Micro-beam Laue alignment of multi-reflection Bragg coherent diffraction imaging measurements - Hofmann, F; Phillips, N; Harder, R; Liu, W; Clark, J; Robinson, I; Abbey, B (International Union of Crystallography, 2017)
Multi-reflection Bragg coherent diffraction imaging has the potential to allow 3D resolved measurements of the full lattice strain tensor in specific micro-crystals. Until now such measurements were hampered by the need for laborious, time-intensive alignment procedures. Here we demonstrate a different approach, using micro-beam Laue X-ray diffraction to first determine the lattice orientation of the micro-crystal. This information is then used to rapidly align coherent diffraction measurements of three or more reflections from the crystal. Based on these, 3D strain and stress fields in the crystal are successfully determined. This approach is demonstrated on a focussed ion beam milled micro-crystal from which six reflections could be measured. Since information from more than three independent reflections is available, the reliability of the phases retrieved from the coherent diffraction data can be assessed. Our results show that rapid, reliable 3D coherent diffraction measurements of the full lattice strain tensor in specific micro-crystals are now feasible and can be successfully carried out even in heavily distorted samples.